1992
DOI: 10.1017/s0021900200043473
|View full text |Cite
|
Sign up to set email alerts
|

Ageing properties of certain dependent geometric sums

Abstract: We study some distribution properties of a random sum of i.i.d. non-negative random variables, where the number of terms is geometrically distributed and not independent of the summands. The results are applied to the system failure time of a one-unit system with a single spare and repair facility. In such a system when the operating unit fails it is immediately replaced by the spare and sent to the repair facility. The system continues operating until the first time when the failed unit has not yet been repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This compound geometric convolution is also an interesting distribution arising in many applied probability models such as reliability, queueing, risk theory; see, for example, Brown (1990), Cai and Garrido (2002), Gertsbakh (1984), Kováts and Móri (1992), Willmot and Lin (1996), and references therein. A special form of (3.1) often appearing in ruin theory and queueing is where F itself is a convolution of the distribution G with a distribution H supported on [0, ∞), i.e.…”
Section: Tails Of Compound Geometric Convolutionsmentioning
confidence: 99%
“…This compound geometric convolution is also an interesting distribution arising in many applied probability models such as reliability, queueing, risk theory; see, for example, Brown (1990), Cai and Garrido (2002), Gertsbakh (1984), Kováts and Móri (1992), Willmot and Lin (1996), and references therein. A special form of (3.1) often appearing in ruin theory and queueing is where F itself is a convolution of the distribution G with a distribution H supported on [0, ∞), i.e.…”
Section: Tails Of Compound Geometric Convolutionsmentioning
confidence: 99%
“…Brown (1990) showed that a geometric sum S N ¼ X 1 þ Á Á Á þ X N always has the NWU aging property whatever the distribution of X 1 is, namely if N is a geometric random variable, then PrfS N 4x þ y j S N 4xgX PrfS N 4yg; xX0; yX0 always holds whatever the distribution of X 1 is. Other distributional properties of a geometric sum can be found in Bon andKalashnikov (2001), Gut (2003), Kova´ts and Mo´ri (1992), Li (2004), Lin and Stoyanov (2002), Willmot (2002), Willmot andCai (2001, 2004), and references therein.…”
Section: Introductionmentioning
confidence: 99%